Unraveling the SES health connection - James P. Smith (Institute for Fiscal Studies (IFS), 2004)
This paper looks at the links between health and socio-economic status. It is generally assumed by non-economists that it is low SES that causes ill health, but this paper asks whether the causation might also work the other way. Even if the direction of causation is that SES mainly affects health, what dimensions of SES actually matter — the financial aspects such as income or wealth or nonfinancial dimensions like education? Finally, is there a life course component to the health gradient so that we may be misled in trying to answer these questions by only looking at people of a certain age — say those past 50. This paper provides my answers to these questions.
Keywords: I12; I18; I31; 330; Health; socio-economic status; causation; Sozialer Status; Soziale Schicht; Gesundheit; USA